Penerapan Model Pembelajaran Berbasis Masalah untuk Mengembangkan Keterampilan Berpikir Kritis Siswa dalam Pelajaran Akidah Akhlak - Rosfiani, Okta; Salsabila, Ratih Salsabila; Khaerani, Najwa Putri; Rachman , Muhammad Rafly Nur; Ariel, Muhammad (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2025)
The lack of internalization of values in daily life is influenced by pupils' poor critical thinking abilities in comprehending the morals and religious values in depth. The purpose of this study is to evaluate how well the problem-based learning (PBL) paradigm fosters students' critical thinking abilities in the Aqidah Akhlak course. The study's background is founded on the qualitative research methodology. Tests of critical thinking abilities, observations, and interviews were used to gather data. In comparison to traditional learning, the study's findings demonstrated that the use of the PBL approach greatly enhanced students' capacity for analyzing, assessing, and resolving issues pertaining to the content of Aqidah Akhlak. Students' favorable reactions to the PBL approach, which is thought to be more engaged and contextual, support this finding. In order to develop students who are not just religious but also analytical and solution-focused, the study's conclusions highlight the significance of innovation in problem-based learning approaches in Islamic religious education.